(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This comprehensive paper delves into the intricate exploration of the concept of free will as conceived by existentialist thinkers. Existentialism, a profound philosophical movement that flourished in the 20th century, emphasizes the significance of individual freedom, authenticity, and personal responsibility in shaping one’s own existence. At the core of this philosophical approach lies the intriguing question of free will and the profound implications it holds for human agency and self-determination. Drawing insights from the works of prominent existentialist philosophers such as Jean-Paul Sartre, Friedrich Nietzsche, and Simone de Beauvoir, this analysis critically examines the diverse perspectives on free will within existentialist thought. By delving into the writings of these influential thinkers, the study seeks to elucidate the multifaceted nature of free will and its role in defining human existence.